2010
DOI: 10.1111/j.1530-0277.2010.01361.x
|View full text |Cite
|
Sign up to set email alerts
|

Amphetamine Self-Administration in Light and Moderate Drinkers

Abstract: Background Light and moderate drinkers respond differently to the effects of abused drugs, including stimulants such as amphetamine. The purpose of this study was to determine whether light and moderate drinkers differ in their sensitivity to the reinforcing and subjective effects of d-amphetamine. We hypothesized that moderate drinkers (i.e., participants that reported consuming at least seven alcohol-containing beverages per week) would be more sensitive to the reinforcing and positive subject-rated effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
(92 reference statements)
1
4
0
Order By: Relevance
“…Long-term d-amphetamine exposure increases ad libitum alcohol consumption in rats (Fahlke, Hansen, Engel, & Hard, 1994). A similar pattern has been shown in human adults: Moderate drinkers worked for more d-amphetamine and reported significantly greater subjective effects than did light drinkers (Stanley, Poole, Stoops, & Rush, 2011). Taken together, these studies provide evidence for cross-sensitization between alcohol and amphetamine.…”
Section: Discussionsupporting
confidence: 74%
“…Long-term d-amphetamine exposure increases ad libitum alcohol consumption in rats (Fahlke, Hansen, Engel, & Hard, 1994). A similar pattern has been shown in human adults: Moderate drinkers worked for more d-amphetamine and reported significantly greater subjective effects than did light drinkers (Stanley, Poole, Stoops, & Rush, 2011). Taken together, these studies provide evidence for cross-sensitization between alcohol and amphetamine.…”
Section: Discussionsupporting
confidence: 74%
“…Sensitivity to the stimulant effects of alcohol is a candidate endophenotype for alcohol use disorders (Quinn and Fromme, ; Ray et al., ). The response to amphetamine has also been associated with various risk factors for alcoholism (Dlugos et al., ; Gabbay, ; Hutchison et al., ; Kelly et al., , ; Stanley et al., ; Stoops et al., , ; White et al., ). The present study extends this work by demonstrating that, in combination with a strong amphetamine response, negative emotionality was associated with more alcohol use.…”
Section: Discussionmentioning
confidence: 99%
“…Stimulant users manifest an exaggerated physiological response to alcohol (Brunelle et al., ), as compared with individuals who have never used psychostimulant drugs. Conversely, moderate alcohol drinkers report greater stimulation to amphetamine than light drinkers (Stanley et al., ; Stoops et al., ). This association is also evident in rodent models: selectively bred rats that self‐administer alcohol display a heightened responsiveness to the stimulant effects of amphetamine (D'Aquila et al., ; Fahlke et al., ; McKinzie et al., ), as compared with nonpreferring rats.…”
Section: The Stimulant Responsementioning
confidence: 99%
See 1 more Smart Citation
“…The drug self-administration procedure has also shown to be sensitive to the influence of pharmacological (e.g., dose and route of administration) and nonpharmacological variables (e.g., behavioral demands and personality differences; see Stoops et al, 2008 for review). Furthermore, drug self-administration has shown to vary as a function of sensation-seeking status, inattention status, drinking status, and gender (Stoops et al, 2007a; Kollins et al, 2009; Vansickel et al, 2010; Stanley et al, 2011). Relevant to the present report, Stoops et al (2007a) reported that individuals high in sensation seeking were more sensitive to the reinforcing effects of d -amphetamine (8 or 16 mg) relative to participants that were low in sensation-seeking status.…”
Section: Introductionmentioning
confidence: 99%